Investigation of HLA-E intracellular transport and antigen presentation - He, W (2023)
Apart from its primary role in presenting signal peptides derived from major histocompatibility complex (MHC) class I molecules to natural killer (NK) cells, MHC-E can also present pathogen-derived peptides to CD8+ T cells to inhibit pathogenesis upon infection. Recent discoveries demonstrated the effectiveness of MHC-E-restricted CD8+ T cell responses in controlling simian immunodeficiency virus (SIV) infection within a vaccine model, which has generated considerable interest in this non-canonical immune pathway.